2019
DOI: 10.4236/fns.2019.108068
|View full text |Cite
|
Sign up to set email alerts
|

Peroxide Index, Trans Fatty Acids, Acrylamide and Polycyclic Aromatic Hydrocarbons (Pah) Contents in Frying Oils and Fried Tuna Fish Involved in “Garba” Production in Côte d’Ivoire

Abstract: This current study aims at determining the profile and contents of degradation compounds produced during the interaction between the frying oils and tuna fish involved in the cooking of "Garba", a street food largely consumed in Côte d'Ivoire. For this purpose, the peroxide index and the neoformed compounds, especially trans fatty acids, acrylamid, polycyclic aromatic hydrocarbons were determined. This trial was carried out on 90 samples of frying oils and fried tuna fish collected from restaurant owners of "G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…19,20,68,82 This view was also shared regarding the increased consumption of a fried-tuna-related food in Abidjan, Cote d'Ivoire. 76 A number of health risk assessments made in different parts of SSA have shown that these exposures have the capacity to bring about carcinogenic and mutagenic risks. 4,67,83,85,87 Despite being a potential health risk, the exposure to food-borne PAHs could also be reduced.…”
Section: Health Risk Assessments Of Pah Contamination In Ssamentioning
confidence: 99%
“…19,20,68,82 This view was also shared regarding the increased consumption of a fried-tuna-related food in Abidjan, Cote d'Ivoire. 76 A number of health risk assessments made in different parts of SSA have shown that these exposures have the capacity to bring about carcinogenic and mutagenic risks. 4,67,83,85,87 Despite being a potential health risk, the exposure to food-borne PAHs could also be reduced.…”
Section: Health Risk Assessments Of Pah Contamination In Ssamentioning
confidence: 99%